2021
DOI: 10.4103/jomfp.jomfp_411_20
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candida albicans and nonalbicans candida resistant species in tobacco users and oral squamous cell carcinoma patients: Comparison of HiCrome agar and automated VITEK 2 system

Abstract: Introduction: Candida is most common fungal pathogen in the immunocompromised and medically ill patients. Higher prevalence of Candida albicans has been reported in tobacco users and oral squamous cell carcinoma (OSCC) patients which may be due to immunosuppression. Recently, emergence of nonalbicans candida (NAC) species resistant to conventional antifungal treatment has been observed that requires accurate identification of organisms at speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Due to the complex and multifaceted nature of carcinogenesis, the role of specific or entire oral microbiomes in oral cancer development and prognosis is still a subject of ongoing research [24]. C. albicans is one of the primary oral microorganisms whose influence on the development of oral cancer has been under evaluation for several decades [11,21,23,[27][28][29][30][31][32][33][34][35][36][37]. The connection between oral mycobiome and carcinogenesis is underscored by the intricate mechanisms through which C. albicans invades keratinocytes and surpasses the innate local defense abilities of oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complex and multifaceted nature of carcinogenesis, the role of specific or entire oral microbiomes in oral cancer development and prognosis is still a subject of ongoing research [24]. C. albicans is one of the primary oral microorganisms whose influence on the development of oral cancer has been under evaluation for several decades [11,21,23,[27][28][29][30][31][32][33][34][35][36][37]. The connection between oral mycobiome and carcinogenesis is underscored by the intricate mechanisms through which C. albicans invades keratinocytes and surpasses the innate local defense abilities of oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…These pioneering reports were further supported by several epidemiological and descriptive studies that revealed significantly higher oral Candida carriage among patients with oral epithelial dysplasia (OED) and OSCC compared to healthy subjects [27][28][29][30][31]. The suggested mechanisms for fungal involvement in oral carcinogenesis include the secretion of potential carcinogens, conversion of pro-carcinogens such as acetaldehyde or nitrosamines, destruction of epithelial barriers by secreted proteolytic enzymes, and excessive chronic inflammation [21,[32][33][34]. Recent in vitro experimental studies reported that OSCC cells secreted significantly more pro-inflammatory cytokine IL-1β when treated with zymosan (ZYM), a component from the cell wall of C. albicans [35], and the progress of OSCC was promoted by the presence of living C. albicans via stimulating the production of matrix metalloproteinases (MMPs), tumor metabolites, and tumor-promoting signal pathways [36].…”
Section: Introductionmentioning
confidence: 96%
“…Nitrosamines, as EGFR activators, can also initiate the activation of a variety of signaling pathways, including the phosphatidylinositol 3‐kinase (PI3k)/Akt/mammalian target of rapamycin (mTOR) pathway, promoting carcinogenesis independently or synergistically (Sonis & Amaral Mendes, 2016). Cigarette smoke increases the susceptibility of oral mucosa to C. albicans by inducing oxidative and redox dysfunction of epithelial cells, which is closely related to the onset of oral cancer (Saxena et al, 2021; Ye et al, 2021). Significantly, Sanjaya et al (2011) proposed that the direct carcinogenic effect of nitrosamines produced by C. albicans is still controversial; for example, immunosuppression may contribute to the activation of the nitrosation potential of C. albicans , which in turn is involved in the induction of oral carcinogenesis.…”
Section: The Mechanisms Of C Albicans In the Malignant Transformation...mentioning
confidence: 99%